Development of fundraising as a technology of social work in Ukraine - Shatylo, Yuliya; Gromova, Olexandra (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2019)
In the article the authors cover a theoretical analysis of scientific literature on the problems of using fundraising as a technology of social work in modern Ukraine. Non-profit organizations act as social intermediaries-implementers of social ideas and programs. They operate between the state, commercial firms and citizens. It is important to develop a comprehensive economy and the state, both for business and society. Fundraising area is a new field of activity for our country. For attraction of resources of sponsors and donors, there are first-rate specialists who are able to replenish the budget of public organizations. The introduction and use of fundraising technology will expand the financial capabilities of social institutions and, consequently, increase the efficiency of their functioning. The dynamics of fundraising development in Ukraine is fast and efficient. An important factor in accelerating this process is the highly skilled training of specialists in this field of activity, which will have the appropriate knowledge, skills, skills and competencies. Fundraising is an almost new area of activity for our country. It has been developed in the US and Europe, where a diverse system of benefits and incentives has been developed for depositors in the social sphere, business entities, foundations or individuals. Free Western Market Traditions Encourage Philanthropy. The social sphere in Ukraine, like no other, needs organized financing from extrabudgetary funds. For a clearer and more professional organization of recruiting sponsors and donors, there are first-rate professionals who can replenish the budget of NGOs. In a market economy, civil society and social initiatives, philanthropy has become a major boon in the form of patronage, sponsorship and support through the provision of grants, donations, material, information resources and more. The proliferation of charity and its form of organized activity has led to the emergence of fundraising, as a science of planning and streamlining actions that will help organized actions for patrons and beneficiaries. Today, fundraising is not sufficiently developed in our country, but in spite of this it has certain prospects. Due to the growing role of civil society organizations, which are able to help the state in solving social problems, it contributes to the development of fundraising in Ukraine. Today the dynamics of fundraising development in Ukraine is noticeably fast and effective. An important factor in the acceleration of this process is the highly qualified training of specialists in this field of activity, who will have the appropriate knowledge, skills.